2010
DOI: 10.1128/iai.01017-09
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Melanoma Cells byMycoplasma hyorhinis: Enhancement by Protease Treatment

Abstract: Mycoplasma hyorhinis (strain MCLD) was recently isolated from a melanoma cell culture. Growth of MCLD was considerably improved by 24 serial passages in a modified Hayflick's mycoplasma medium. Transmission electron microscopy showed that MCLD exhibits a polymorphic appearance, with ovoid or elongated cells frequently harboring an electron-dense core at one of the poles. Adherence of M. hyorhinis to melanoma cells followed saturation kinetics. Furthermore, although M. hyorhinis has been considered to remain at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…Changes in host cell lipid turnover occur as a result of M. penetrans binding and/or invasion of Molt-3 lymphocytes [40]. These changes include the accumulation of DAG and the release of unsaturated fatty acids, predominantly long-chain polyunsaturated ones such as docosahexanoic acid (C22: 6,40]. Nonetheless, metabolites of phosphatidylinositol were not detected.…”
Section: Invasion Of Host Cellsmentioning
confidence: 97%
See 2 more Smart Citations
“…Changes in host cell lipid turnover occur as a result of M. penetrans binding and/or invasion of Molt-3 lymphocytes [40]. These changes include the accumulation of DAG and the release of unsaturated fatty acids, predominantly long-chain polyunsaturated ones such as docosahexanoic acid (C22: 6,40]. Nonetheless, metabolites of phosphatidylinositol were not detected.…”
Section: Invasion Of Host Cellsmentioning
confidence: 97%
“…Imaging single infected HeLa cells revealed that invasion is both time and temperature dependent. Penetration of melanoma cells by M. hyorhinis has been observed as early as 30 min after infection [6], whereas invasion of cultured HEp-2 cells by M. penetrans has been shown to begin after 2 h of infection [36].…”
Section: Invasion Of Host Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Namiki and colleagues reported the occurrence of M. hyorhinis infection in malignant of the benign human prostate (BPH-1) in cell culture (10, [17][18]. Besides, Urbanek and his colleagues, using serological test showed positive tests of M. hyorhinis for more than thirty percent benign prostatic hyperplasia (BPH) and more than fifty percent prostatic cancer tissues (19).…”
Section: Introductionmentioning
confidence: 99%
“…Dong and his research group in 1980 performed studies on monoclonal PD4 antibody via mice immunization with the gastric cancer cell, then the mycoplasma antigen was detected by PD4, which is a lipoprotein of M. hyorhinis called P37 and does not have any homology with human proteins (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%